Vintage analysis as a basic tool for monitoring credit risk - Siarka, Paweł (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
Among many tools used by bankers in the process of credit risk management, vintage analysis is the most often applied. Its simplicity and clarity of interpretation of the results means that banking professionals call it “basic analysis”. In this article, the concept of vintage analysis is presented, along with the right way to get interpretations of results. The author demonstrates the usefulness of vintage analysis in the context of the back-testing procedure recommended in New Basel Capital Accord. In addition, there is also a discussion of an aspect of the limits structure as a part of the credit risk management process.
Mathematical Economics, 2011, Nr 7 (14), s. 213-228
Keywords: credit risk; retail loans; probability of default